DIFFERENCES OF COPING STRESS ON MALE AND FEMALE NURSES - Prety Lestarianita; M. Fakhrurrozi M. Fakhrurrozi (Universitas Gunadarma, 2007)
The aim of this study is to know the differences of coping stress on the male dan female nurses. The participant of this study are 50 male nurses and 50 female nurses with the age range from 25 – 36 years old and already work as a nurse in 6 mounths. The result done by the T-test shows that there are no differences of coping stress(problem-focused coping, emotion-focused coping and religion-focused coping stress) on the male and female nurses.Key words: coping stress, nurse